Investigation of Hereditary Thrombophilia in Women with Recurrent Fetal Loss in LUMHS Hyderabad; A Descriptive Cross-Sectional Study - Kaynat Ilyas, Sughand Khaskheli, Benazeer Bhatti, Riyasat Ahmed Memon, Rameez Iqbal Memon, Samina, Marvi (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate the role of Antithrombin, Protein C, Protein S and Factor V Leiden in recurrent pregnancy loss and to compare the cause of hereditary thrombophilia among women with recurrent pregnancy loss. Methods: Sixty patients with two or more pregnancy loss having ages 19-40 years were included in the descriptive cross-sectional study was performed at Diagnostic and Research Laboratory LUMHS Jamshoro/Hyderabad and Department of Pathology LUMHS, Jamshoro from January 2020 to December 2020. While patients with liver disease, uterine Fibroids, Cardiac disease, congenital abnormalities associated pregnancy loss were excluded. Total 10 ml blood was taken and distributed in EDTA tube and in sodium citrate. CBC was performed on automated CBC analyzer Sysmex CA 1000. PT, APTT performed on Sysmex CA 600. Antithrombin screening done by INNOVANCE Antithrombin Kit. Protein C activity measured by Berichrome Protein C Kit. Protein S screened by Siemens Protein S Ac kit. Factor V Leiden was done by using Pro C global kit with factor V deficient plasma. Quality control and standard curves were performed as per kits instructions. Results: In our study of sixty women with recurrent fetal loss, mean ages were 29.3± 4.9. The mean number of fetal loss among patients was (3.1± 1.5) while parity was (1.6 ± 1.2). Among these patients mean platelets were (302.6 ± 74.9), PT was (11.9 ± 0.14), APTT was (27.1 ±1.3). Protein C was found in 12 (20%), while 19 (31%) patients had Factor V Leiden. Whereas, Protein S was found in 3 (5%) patients. Antithrombin was not detected in any patients. Conclusion: Our research based on the results concludes that Factor V Leiden had a significant association to the women with recurrent fetal loss and it could be a cause of recurrent pregnancy loss. Keywords: Hereditary thrombophilia, Recurrent fetal loss, Factor V leiden.